(untitled) (Fiep Bulletin - online, 2014)
The worker’s health as a complex and charged with meaning theme, not only in the cultural and economic context, but also in the anthropologic and social background, requires more multi, inter and transdisciplinary actions in search of resolution for problems originated from the work relations and environment. This article illustrates the report of a case study experienced in Centro Universitário Feevale, RS - Brazil. Through integrated actions between Physical Education, Physiotherapy and Ergonomics professionals, it was possible to achieve excellent results in terms of effectiveness of a larger and more including program - the Quality of Life at Work program (QVT Feevale). The results achieved from Labor Gymnastics and Ergonomics actions benefit the internal public of the Institution, impacting their health and quality of life, also contributing in a direct way for the growth of the Institution’s image. From the experience narrated in this article, it is evident that a multi, inter and transdisciplinary integrated work needs to cease being “mere fallacy” to become reality. Only through an integrated work between professionals of the several courses and institutes, it was possible to collect the mentioned results.